Design, power quality analysis, and implementation of smart energy meter using internet of things. (July 2021) - Kumar, L Ashok; Indragandhi, V.; Selvamathi, R; Vijayakumar, V.; Ravi, Logesh; Subramaniyaswamy, V
Abstract: Effective energy consumption plays a massive role in the growth of smart-grid in the power system. But it is difficult to monitor and control the existing energy meter while using non-linear loads. The programmed control affects the quality of power and leads to distortion of current and voltage waveforms. A smart energy meter is proposed to overcome this glitch based on the Internet of Things (loT). The proposed smart energy meter controls and calculates energy consumption using the Fast Fourier Transform (FFT). The sensed voltage and current values are fed into the ATMega328-P microcontroller, and the various power-related parameters are calculated by the instantaneous power calculation technique. The experimental values are verified using three standard meters: Fluke 317, Mecho 5760, and Fluke 434 series-II power quality analyzer. The data are uploaded to various fields of the Thing Speak cloud platform for efficient monitoring.